Serological Evidence of Exposure to Leptospira spp. in Veterinary Students and Other University Students in Trinidad and Tobago - James, Ambrose; Siele, Kingsley; Harry, Neeka; Suepaul, Sharianne; Stewart-Johnson, Alva; Adesiyun, Abiodun (Interdisciplinary Perspectives on Infectious Diseases, 2013)
The study compared the serological evidence of leptospirosis in 212 students in four schools (veterinary, dental, advanced nursing education and pharmacy) of the University of the West Indies (UWI), by testing for IgG immunoglobulins to Leptospira spp. using the enzyme-linked immunosorbent assay (ELISA) and the microscopic agglutination test (MAT). Overall, of 212 students tested by the ELISA, 12 (5.7%) and 31 (14.6%) were positive and borderline, respectively. Amongst the 113 veterinary students 11 (9.7%) and 19 (16.8%) were seropositive and borderline respectively compared with nonveterinary students with corresponding values of 1 (1.0%) and 12 (12.1%). The frequency of serological evidence of leptospirosis by the ELISA was statistically significantly (P<0.05; χ2) higher in veterinary students, 26.5% (30 of 113) than in nonveterinary students, 13.1% (13 of 99). By the MAT, the seropositivity for leptospirosis was similar for veterinary students, 7.1% (8 of 113) and nonveterinary students, 7.1% (7 of 99). For veterinary students, the prevalent infecting serovar was Icterohaemorrhagiae Copenhageni while amongst nonveterinary students, the prevalent serovar was Australis Rachmati. Being a veterinary student was the only risk factor that was significantly associated with Leptospira infection indicating that veterinary students need to be cognizant and to practise preventive measures for leptospirosis.